A study of time in twentieth-century musical ritual: a musico-philosophical development from Debussy (through Stravinsky, Webern and Messiaen) to Stockhausen, in the utilization of musical time and ecstatic musical involvement for the purpose of transcending the consciousness of Real Time and Space. - Pienaar, Sarah Johanna (College of Music, 2024)
The study rests on a fundamental premise: The artist, in his art, reflects the consciousness of his time. "Man of a given time and place, in creating the ideological and artistic systems by which he has expressed himself, has projected into his philosophy, his literature, and his art a reflection of t he same fundamental preoccupations. These preoccupations, which may be expressed in various media, are those of his time and of its material, moral, economic, social and spiritual circumstances. The genius of the individual serves only to give a more universal and eternal significance to them through the amplitude 1 and quality of his vision."